Boundary conditions to the effect of fluency and comprehension on AAD when targeting Hispanics vs Whites with single meaning vs polysemous slogans. Issue 3 (11th May 2015) - Zúñiga, Miguel Angel; Torres, Ivonne M.; Niculescu, Mihai
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to show that high ethnic identifying Hispanics and Whites pursue different routes discussed in the Elaboration Likelihood Model when processing single meaning versus polysemous slogan ads. The authors found that high ethnic identifying Hispanics used the peripheral route (processing fluency) to a higher extent compared to Whites who used the central route (comprehension) to process ads. Design/methodology/approach – In this study, 310 undergraduate students of a Southwestern university were randomly assigned to one of two conditions (slogan: single meaning vs polysemous) in a between-subjects experimental design. Subsequently, participants responded to statements measuring constructs of interest and demographics. Participants were debriefed at the end of the survey. Findings – It was found that high ethnic identifying Hispanics used the peripheral route (processing fluency) to a higher extent compared to Whites who used the central route (comprehension) to process advertisements. Results suggest that while polysemous slogans are similarly interpreted by subject independent of their ethnic identification score, for single-meaning slogans, the impact of comprehension on attitudes toward the advertisement (AAD) is significantly different for low (vs high) ethnic identification individuals. Research limitations/implications – A future study needs to study brand attitudes and purchase intentions. Additionally, strategies in developing advertisements that influence comprehension or processing fluency need to be studied. Practical implications – This paper's contribution to the processing fluency literature is to propose that ethnic identification and slogan meaning are variables that have great potential in influencing consumers' perceptions about advertisements. Advertisers will have these variables to control to maximize the persuasiveness of advertisements. Originality/value – Minimal research focusing on polysemy in marketing exists. In advertising, comprehension is commonly studied, leaving processing fluency out. This research addresses the issue by focusing on how single-meaning and polysemous slogans are processed (via comprehension or processing fluency) by consumers and how their ethnic identification affects their AAD.